Impact of covid-19 pandemic on microfinance banks in Nigeria (2022)
The outbreak of the novel coronavirus (COVID-19) has created existential challenges to the Nigerian economy especially the microcredit delivery system and microfinance institutions that serve the poor and vulnerable groups in the country. The study investigated the impact of Covid-19 pandemic and the government mandated lockdown on the activities of microfinance banks (MFBs) in Nigeria using the exploratory and content analytical technique. The study found that all the key performance indicators (KFIs) of MFBs have been negatively affected by the Covid-19 pandemic. In particular, the study found that the asset quality of MFBs has deteriorated with high level of portfolio at risk (PAR). The pandemic has also affected the capital adequacy of MFBs especially the state and unit MFBs due to increased and large provisioning for loan losses. In consequence, the shareholders’ funds for most of the state and unit MFBs have been seriously eroded and impaired by losses. Among others, the study recommended for an urgent regulatory forbearance and injection of liquidity in the sector by the Central Bank of Nigeria through a bail-out and to enlarge the CBN discount window to accommodate eligible MFBs to discount facilities that are hitherto only available to deposit money banks (DMBs).